Towards Sustainable Antibiotic Use in Aquaculture and Antimicrobial Resistance: Participatory Experts' Overview and Recommendations - Daniela R. Farías; Rolando Ibarra; Rodrigo A. Estévez; Michael F. Tlusty; Oskar Nyberg; Max Troell; Ruben Avendaño-Herrera; Wendy Norden (MDPI AG, 2024)
Notably, 56 worldwide experts gathered for the Antimicrobial Assessment on Global Aquaculture Production (AGAP) series of workshops to (1) evaluate the current state of knowledge on antimicrobial use and identify existing gaps; (2) formulate strategies to identify ecologically relevant impact indicators and establish thresholds for assessment; (3) identify pivotal socioeconomic factors and effective governance mechanisms essential for implementing monitoring practices in aquaculture and extending them across sectors and countries for aquaculture sustainability; (4) develop pathways to enhance our comprehension between antibiotic use in aquaculture and antimicrobial resistance; and (5) explore potential antibiotic monitoring tools that can be universally adapted and implemented across region and sectors. The main outcomes were a roadmap for establishing investigation priorities on the relevant topics regarding antibiotic use in aquaculture, socioeconomic drivers for using antibiotics and behaviors that need more robust and transparent regulatory frameworks to guide farmers, training on antimicrobial use, and access to veterinarians and extension services agents for education. Overall, the workshop evidenced the power of collaboration in addressing complex global challenges to achieve sustainable aquaculture. Despite diligent efforts, some constraints may have inadvertently narrowed the possibility of having more experts and left some pertinent topics unaddressed, but they are needed in the discussion.